2005
DOI: 10.3182/20050703-6-cz-1902.00868
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Algorithms in Control System Engineering

Abstract: This paper introduces the session describing the state-of-the-art in the application of evolutionary computation in control system engineering. Evolutionary methods such as genetic algorithms (GAs) and genetic programming (GP) are particularly suitable in problems for which conventional optimizers are inefficient or inappropriate, rather than simply as an alternative to conventional optimization. This session will be of interest to the control engineering community as a whole, and will provide an educational b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…In [100], Abd Samad introduced a good survey about the usage of EC algorithms in the field of system identification in the last 40 years. In addition, EC algorithms have been implemented for critical applications: on-line and off-line control system engineers [101]. In [102], Fleming et al introduced a survey of using EC algorithms in control system, and they concluded the importance of EC algorithms in control system applications.…”
Section: Advantages Limitations and Applications Of Ec Algorithmsmentioning
confidence: 99%
“…In [100], Abd Samad introduced a good survey about the usage of EC algorithms in the field of system identification in the last 40 years. In addition, EC algorithms have been implemented for critical applications: on-line and off-line control system engineers [101]. In [102], Fleming et al introduced a survey of using EC algorithms in control system, and they concluded the importance of EC algorithms in control system applications.…”
Section: Advantages Limitations and Applications Of Ec Algorithmsmentioning
confidence: 99%
“…Kawabe et al, (1996), Krohling & Rey (2001), Sekaj & Veselý (2005). The second group of methods applies simulation-based closed-loop evaluation of the model as in Khatib (1999), Mitsukura et al (1999, Sweriduk et al (1999), Sekaj (1999), Herrero et al (2002, Lewin (2005), Yang (2005), Sekaj (2011). Survey of evolutionary-based control system designs can be found in Lewin (2005) or Sekaj (2011).…”
Section: Introductionmentioning
confidence: 99%
“…It can be used in the controller design area for various purposes. A survey of evolutionary-based control system designs can be found in [10] or [16]. Note that also other types of evolutionary algorithms can be used instead of the GA [5].…”
Section: Introductionmentioning
confidence: 99%